RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN ONLINE PADA SEKOLAH CLARISSA BERBASIS WEB DI KOTA BATAM - napitupulu, maida; Arnomo, Sasa Ani (Computer Science and Industrial Engineering, 2021)
Online registration for new students is a process that exists in educational institutions such as schools that carry out automatic selection. Technological developments from time to time are increasingly sophisticated, various problems can be done with the presence of today's technology. technology and information become solutions to complete work or facilitate work effectively and efficiently. The school registration information system that was built can help the Clarissa Batam school in data processing and submitting registration information and simplify the process of working on Clarissa school staff. In this study, the data collection process was carried out using the methods of observation, interviews, and literature studies. The system design method used is Extreme programming where the stages are planning, designing, coding, testing the system. The website design uses the Codelgniter 4 framework, Bootstrap 4, and MySQL in order to shorten the processing time with satisfactory results. With the development of this information system, it is hoped that it can be a solution to the problems faced at the Clarissa School of Batam City in conveying registration information and data processing and other features.